2013
DOI: 10.1039/c3cp44390f
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the shortcomings of the Nernst–Planck model

Abstract: This is a study on electrolytes that takes a thermodynamically consistent coupling between mechanics and diffusion into account. It removes some inherent deficiencies of the popular Nernst-Planck model. A boundary problem for equilibrium processes is used to illustrate the features of the new model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
183
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(186 citation statements)
references
References 15 publications
3
183
0
Order By: Relevance
“…Flux relation.-The most simple relation between the diffusional flux j α and the chemical potentials μ α in order to ensure a non-negative entropy production is 23,35 …”
Section: Journal Of the Electrochemical Society 164 (11) E3671-e3685mentioning
confidence: 99%
“…Flux relation.-The most simple relation between the diffusional flux j α and the chemical potentials μ α in order to ensure a non-negative entropy production is 23,35 …”
Section: Journal Of the Electrochemical Society 164 (11) E3671-e3685mentioning
confidence: 99%
“…Nonequilibrium thermodynamics [13] suggests that the chemical potentials of the species have to be regarded as driving forces, allowing to describe finite ion size effects in the constitutive relationship between chemical potential and concentration. The authors of [14] recently confirmed that in order to derive a thermodynamically consistent model it is necessary to include the dependency on the pressure into this relationship [4].…”
Section: Introductionmentioning
confidence: 99%
“…In Section 2, the Nernst-Planck-Poisson-Navier-Stokes system for an ideal incompressible mixture is introduced in a formulation equivalent to that provided in [14]. Then, constitutive relationships between chemical potential, pressure and concentration are introduced for four cases: the classical Nernst-Planck equations leading to the Gouy-Chapman double layer model, the excluded volume models after Bikerman and Freise [3,4], the ideal incompressible mixture [14], and -as it is closely related -Fermi-Dirac statistics for semiconductor problems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations